Antibody response to 1.0 and 0.5 mL doses of an inactivated bacterial vaccine against bovine respiratory disease in young Holstein calves: a field trial - Mori Kazusa; Kato Toshihide; Kosenda Keigo; Yokota Osamu; Ohtsuka Hiromichi (Journal of Veterinary Research, 2023)
Early vaccination of cattle with an inactivated commercial bacterial vaccine against bovine respiratory disease has been reported to increase antibody production and can alleviate the disease. However, its dosage has been little investigated in young Holstein calves. This study addresses the need to establish guide values for vaccine dosage in these animals.